Evaluating 90Sr contamination in seafood and human exposure risks near Zhejiang nuclear power plants, China - Zhou, Lei; Wang, Rui; Zou, Hua; Ren, Hong; Wang, Peng; Yu, Shunfei; Lai, Zhongjun; Cao, Yiyao (Frontiers in Public Health, 2025)
ObjectiveThis work aims to assess the impact of three nuclear power plants (NPPs) in Zhejiang Province on the levels of 90Sr in surrounding seafood, and to evaluate the associated health risks, providing a scientific basis for operational monitoring and contributing essential baseline data for nuclear emergency preparedness.MethodsFrom 2021 to 2023, the specific activities of 90Sr in five types of seafood (fish, shrimp, mussels, crabs, and algae) were monitored in the three NPPs, compared with Zhoushan City, which has no NPP, and the annual effective dose (AED) was estimated.ResultsThe results show that the mean specific activities of 90Sr in fish, shrimp, mussels, crabs, and algae around the NPPs were found to range from 0.09 to 0.76 Bq/kg, 0.03–0.30 Bq/kg, 0.01–0.22 Bq/kg, 0.11–1.04 Bq/kg, and 0.02–0.95 Bq/kg, respectively. According to the Kruskal-Wallis test, there was no statistically significant difference between the 90Sr specific activities in seafood from the three NPPs and Zhoushan. The AED due to 90Sr intake from seafood for residents living around the three NPPs and Zhoushan are much lower than the recommended threshold of 1.0 mSv/y.ConclusionThe comprehensive monitoring results demonstrated that the 90Sr levels were at background levels and remained stable, consistently well below the limits of the relevant food safety standards, and the dose burden on the population was slight, indicating that the operation of the NPPs in Zhejiang Province did not have a significantly impact on the local seafood.